Marketing Distribution Using Mobile Technology - Saad, Salah Eldeen Ali (2009)
The following project looks into how the development process will take place for a prototype for marketing using new technology such as mobile commerce when a company called Aljawdh is doing business with its customers. The prototype will show the functionality of the interface being used from a computer screen as well as when it is being used on a mobile device. Aljawdh will be changing it system that it is using from a manual system to a computerized system. The problem areas were with the functions of the manual system that was being used by the company in keeping records of their products that were on promotions and those that were not. The problems that were faced by Aljawdh Company were adequately solved by the introduction of the computerized system that could be used to notify customers for products that were on promotions as well as keep records of all the products that the company had. The methods that were used to solve the major problems that the company was facing was to introduce the system that could send SMS and MMS to customers phones when being notified of the products that will be on promotion. The other method of solving the problem was to have a system that could be linked to suppliers so that they could be easily notified if there is any reorder required of products that would have been finished. In coming up with the required system it was found out that not all the required functions and non-functions of the system could be implemented due to inadequate information give during requirements gathering that was carried out. The prototype had also some delays when it comes to linking up with the database to update and delete information in the database.